Education in the Era of Social Media Trends: Development of Instagram Feed Learning Media Using Canva on Biology Material - Harahap, Lia Junita; Solihin, Solihin (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Social media has become an important part that cannot be separated from the education system, not only in Indonesia but throughout the world. This is a change in mindset in learning and sharing knowledge, including Biology. Biology requires students to be able to think at a high level, understand all concepts, and must be able to relate them to natural events or happenings or to other biological concepts. Learning media that can utilize social media is one of the supports for an optimal learning process. Using Canva-based Instagram Feed learning media will make it easier for students to understand and make decisions. This research aims to develop Instagram Feed media via Canva on valid Biology material. The method used in this research is Research and Development (RD) with the ADDIE model. Stages include Analysis, Design, Development, Implementation, and Evaluation. However, this research only reached the development stage. The products that have been developed are then validated by media experts and material experts. The results show that the learning media developed has an average of 87.00, which means that the Canva-based Instagram Feed media developed is feasible or suitable for use in the learning process.